Study of the Colocated Dual-Polarized MIMO Capacity Composed of Dipole and Loop Antennas - Dazhi Piao; Xingning Jia; Lingyu Yang; Qingxin Guo; Yi Mao; Zengrui Li (International Journal of Antennas and Propagation)
The colocated dual-polarized dipole (DPD) and dual-polarized loop (DPL) MIMO channel performances are compared. Computation results show that, for the ideal electric and magnetic dipoles, the dual-polarized MIMO systems have identical channel capacity. But the contour plots of the capacity gain of the realistic DPD and DPL are different, due to the difference in antenna patterns. The cumulative distribution function (CDF) of the capacity gain in the two-mirror (TM) channel shows that, for small distance, the capacity gain obtained by the DPD is obviously smaller than that of the DPL, but, with the increase of the distance, the difference gets smaller. A DPL with low mutual coupling is fabricated. Measured results show that high MIMO capacities can be obtained by this DPL in both the anechoic chamber (AC) and the realistic office room. The capacity gain of the DPL antenna is 1.5–1.99, which basically coincides with the theoretical and numerical results. Furthermore, the capacity of the virtual DPL antenna with no mutual couplings is also investigated. It is shown that, in the AC, the mutual coupling will generally decrease the dual-polarized MIMO capacity; however, in the office room, the effect of mutual coupling is not always negative.